2378. Resolution of Signs and Symptoms (S&S) of Acute Bacterial Skin and Skin Structure Infections (ABSSSI) With Delafloxacin (DLX) IV/Oral Therapy. (26th November 2018) - Pullman, John; O'Riordan, William; Lawrence, Laura; Quintas, Megan; Tseng, Carol; Cammarata, Sue K
Abstract: Background: Delafloxacin, a fluoroquinolone antibiotic with Gram-negative and Gram-positive activity including MRSA, was approved for treatment of ABSSSI. In a phase 3 ABSSSI trial, DLX was non-inferior to VAN/AZ in both objective and clinical response endpoints. Clinical signs and symptoms (S&S) and lesion size measurements also were evaluated in this trial. Methods: A multicenter, double-blind trial of adults with ABSSSI patients randomized 1:1 to receive either DLX monotherapy 300mg q12h IV with switch to oral 450 mg q12h or vancomycin (VAN) 15 mg/kg (actual body weight) with aztreonam (AZ) for 5–14 days. AZ was discontinued once Gram-negative infection was excluded in the VAN arm. The presence or absence of clinical S&S were collected at each evaluation timepoint. Patients with complete resolution of S&S were classified as complete cures. Lesions were measured by digital planimetry. Patient-reported pain was recorded by numerical rating scale (NRS; 0=no pain, 10= worst pain). Assessments were completed at baseline, during and at end of treatment (EOT), at Follow-up (FU day 14) and Late Follow-up (LFU day 21–28). Results: 850 patients were randomized in United States, Europe, Asia and Latin America. 63% were male with mean age 51 years. 48% had cellulitis, 25% abscesses, 26% wound and 1% burn infections. Baseline erythema and induration were reported in 100% and 93% of patients, respectively. Mean area of erythema and induration at baseline was 353 and 138 cm 2 respectively. Most common locations for lesions were lower extremities (56%) and upper extremities (24%). S. aureus was the most common isolate. Mean days of treatment was 7 days in either group. DLX and VAN/AZ patients had comparable impact on S&S with complete resolution in 42% vs. 45% at EOT, and 58% vs. 60% at FU, and 68% vs. 71% at LFU respectively. DLX was comparable to VAN/AZ in percent reduction in erythema over time (figure). There was a mean reduction of 58% vs. 53% at 48–72 h, 90% vs. 87% at EOT, and 98% vs. 97% at LFU for DLX and VAN/AZ respectively (figure). Baseline mean pain scores were 7/10 with scores of 1/10 at EOT and 0.5/10 at FU for both treatment groups. Conclusion: Treatment with DLX and VAN/AZ provided equally rapid improvement in clinical signs and symptoms in ABSSSI with comparable reductions in S&S, lesion size and pain score. Disclosures: J. Pullman, Melinta Therapeutics, Inc.: Investigator, Research support. W. O' Riordan, Melinta Therapeutics, Inc.: Investigator, Research support. L. Lawrence, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. M. Quintas, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. C. Tseng, Melinta Therapeutics, Inc.: Consultant and Research Contractor, Consulting fee. S. K. Cammarata, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary.